L’apparent paradoxe de la notoriété actuelle de Karl Polanyi - Servet, Jean-Michel (Revue Francaise de Socio-Economie, 2018)
Pour qui est convaincu qu’un auteur n’a rien d’un esprit tombé du ciel et qu’un écrit particulier ne peut être produit dans n’importe quelles conditions, comme pour qui pense que son biographe doit absorber les conditions économiques, sociales, politiques, morales et intellectuelles spécifiques de sa vie, ses racines familiales, ses réseaux de proches et d’amis, ses collaborations professionnelles, les débats scientifiques auxquels il a participé et jusqu’à ses traits psychologiques et somatiques, Karl Polanyi. A life on the left, la biographie que Gareth Dale, senior lecturer à la Brunel University de Londres, a consacrée à l’auteur de La Grande Transformation, peut être considérée comme un modèle. Elle remplit en effet largement l’objectif qu’il se donne : « met[tre] l’accent sur le processus de formation intellectuelle de Polanyi, car il a interagi avec l’environnement social et géopolitique changeant », et elle a été en cela largement saluée par ceux et celles qui en ont rendu compte. À la différence d’autres travaux moins bien documentés car réalisés par des biographes ignorant le hongrois et l’allemand et réduits à une documentation essentiellement en langue anglaise, les compétences linguistiques (pour ce qui est de l’allemand) associées à une subvention lui permettant de disposer de la traduction de textes en hongrois ou de leurs résumés, de ce spécialiste de l’œuvre de Polanyi et plus généralement des rapports internationaux et politiques de l’époque où ce dernier a vécu lui ont permis de saisir avec finesse le contexte global et personnel de Polanyi…
Sociology
Keywords: Karl Polanyi: A Life on the Left (Book); book review

Penser la pluralité des monnaies à partir de Polanyi : un essai de typologie - Blanc, Jérôme (ERES, 2014)
A large number of currencies has emerged for thirty years, far beyond the national currencies alone. It includes systems created by groups of citizens, others by territorial communities, and others by private companies for their own benefit. These currencies take various forms, ranging from electronic money on smart cards to settlement systems ...
Sociology
Keywords: currencies; modern currencies

Maintenir l'ordre économique, Maintaining the economic order - Gayon, Vincent; Lemoine, Benjamin (Politix, 2014)
La sociologie des politiques économiques défendue dans cet article prend pour objet le travail permanent de construction, de naturalisation et de maintien de l’ordre économique déployé par une multitude d’acteurs et d’instruments techniques. Il s’agit d’ouvrir des enquêtes sur la façon dont prennent forme les processus de désencastrement et de réencastrement de l’économie vis-à-vis des institutions politiques et sociales. Cette piste est suivie en quatre temps. D’abord en soulignant la portée sociogénétique de l’œuvre de Karl Polanyi et son insistance sur l’émancipation disputée et incertaine des pratiques de production et d’échange à l’égard des tutelles traditionnelles. Puis en montrant comment l’invention de l’économie en tant que sphère d’activité autonome suscite foule de résistances et de « mondes économiques renversés », opposant leurs propres normes aux « lois » supposées de l’économie. La configuration de l’après Seconde Guerre mondiale est revisitée comme un laboratoire exemplaire de réencastrement politico-étatique de l’économie. Le désencastrement néolibéral des marchés financiers à l’échelle internationale recompose ensuite les comptes de la puissance publique et privée. Ces ordres économiques balisent simultanément des zones d’accès et, réciproquement, de non-droit à la discussion publique et politique., ENG: The sociology of economic policies argued in this article investigates the permanent work of construction, naturalization and maintenance of the economic order made by a multitude of actors and technical instruments. It consists in describing how the doctrinal project of economy disembeddedness takes shape, detaching itself from the political and social institutions. This program is developed through four steps. First, by offering a constructivist reading of Karl Polanyi writings and highlighting the author’s insistence on the uncertain and contested process of production and exchanges’ practices emancipation vis-à-vis traditional guardianship. Then, by showing how the invention of the economy as an autonomous sphere of activity raises crowd resistance and « reversed economic worlds » settling their own standards and laws by opposition to the economy « rules » and values. The after World War Two configuration is revisited as an exemplary laboratory of Politics and State re-embeddedness of the economy. Then, neoliberal disembeddedness of global capital markets reshapes accounts of public and private powers. These economic orders simultaneously mark out areas of access to and, conversely, of non-entitlement to public and political discussion.
Sociology
Keywords: constructivist; embeddedness

Cartographie des échanges - Steiner, Philippe (Nouvelles Perspectives en Sciences Sociales, 2014)
In this article, I examine the main typologies of transaction that have been built from Auguste Comte to Karl Polanyi, Marcel Mauss, and Philippe Descola. Then, I suggest to reconsidering Polanyi's typology, the most common in contemporary economic sociology, and to limit the time span to modern societies. Accordingly, it is possible to map seven forms of transaction and the related institutions at work in our societies. In conclusion, the political consequences of the existence of these different forms of transaction are highlighted. (English)
Sociology
Keywords: don; exchange; gift; héritage; inheritance; marché; market; solidarity; solidarité; échange

Le don fondateur du lien social, le cas de l'économie de marché - Lasida, Elena (Transversalités, 2014)
Le don et l’échange marchand sont généralement opposés. Pourtant, l’un et l’autre apparaissent comme fondateurs du lien social dans la mesure où l’on prend en compte la relation qu’ils créent au niveau interindividuel et collectif. Le don apparaît ainsi associé à une certaine forme de réciprocité et le marché à une certaine forme de gratuité., Gift and commodity exchange are generally opposed. But both appear as founders of the social bond when we consider the relationship they create between people and in society. The gift is thus associated with some form of reciprocity and the market with some form of gratuitousness.
Sociology; Economics
Keywords: don; lien social; marché; relation; réciprocité; valeur; économie; économie sociale et solidaire

La société contre le marché - Skornicki, Arnault (The Life of Ideas, 2012)
A propos de : Karl Polanyi, La Subsistance de l'homme. La place de l'économie dans l'histoire et dans la société, Flammarion
History; Sociology
Keywords: capitalisme; commerce; marché

Le concept de « marchandise fictive », pierre angulaire de l'institutionnalisme de Karl Polanyi ? - Postel, Nicolas; Sobel, Richard (Revue de philosophie économique, 2011)
The notion of “fictitious commodities” is not simply a convenient heterodox slogan to criticize the radical limits of any trade system and the analytical limits of the dominant theory. It is rather the foundation of the institutional perspectives that underlie all Karl Polanyi’s sociohistoric analyses. This article explains and articulates both the theoretical level using the institutional approach to commodities and a philosophical level using a broad definition of the economy. There is, however, a limit to the notion of the institution, which connects both levels: it is not articulated practically such that the potential and critique of this construct may be weakened.
Sociology; Economics
Keywords: capitalisme; institution; marchandises fictives; raison pratique; économie substantive

Avez-vous lu Polanyi ? - Maucourant, Jérôme (HAL, 2011)
"Cette étude présente le parcours intellectuel de Karl Polanyi (1886-1964), à la croisée de l'économie, de l'histoire et de la sociologie, et propose une synthèse de l'ensemble de son oeuvre." Postface accessible en ligne : [ http://www.contretemps.eu/lectures/bonnes-feuilles-avez-vous-lu-polanyi-j%C3%A9r%C3%B4me-maucourant-postface ]
Economics; Sociology
Keywords: Great Transformation; The (Book); La Grande Transformation; critique and interpretation; critique et interprétation; libéralisme; économie politique

Polanyi contre Freeman. (Polanyi against Freeman. With English summary.) - Postel, Nicolas; Sobel, Richard (Revue de la Regulation, 2011)
The dominant approach of CSR is based on the concept of "stakeholders" (R. E. Freeman). More than a theory, it is a slogan which irrigates as much the scientific discourse as the manager and political discourses. We can make two readings of this slogan. The first one, which is very reducing for us, consists on the deconstruction of the firm as institution and its replacement by a market representation based on bilateral exchanges between rational individuals. The second one, more promising in order to identify the potentialities of CSR in terms of regulation, intends to found the notion of stakeholder on a theory of actor and institution. It is the position which we defend by mobilizing Karl Polanyi's institutionalism.
Sociology; Economics
Keywords: Marxian; Sraffian; business objectives of the firm; corporate culture; current heterodox approaches: institutional; current heterodox approaches: socialist; diversity; evolutionary; social responsibility

Au-dela de la dichotomie marche-institutions: L'institutionnalisme de Douglass North face au defi de Karl Polanyi. (With English summary.) - Didry, Claude; Vincensini, Caroline (Revue Francaise de Socio-economie, 2010)
On the basis of the "challenge" North (1977) identified in the works of Polanyi, we propose to outline the originality of North's institutionalism, especially in comparison with "new institutionalism" in economics as well as in sociology. Far from endorsing the dichotomy between market and non market dimensions of economic activities at the basis of the analyses of Williamson and Granovetter, North's definition of institutions as "rules of the game" allows him to conceive of institutions as the institutional foundations of the market and therefore as explanatory principles of historical dynamics.
Sociology
Keywords: Austrian; current heterodox approaches: institutional; evolutionary; history of economic thought; history of economic thought since 1925; institutional

Polanyi, lecteur de Marx - Maucourant, Jérôme (2009)
En premier lieu, c'est la critique du capitalisme et du fascisme comme la prolongation toujours possible de celui-ci qui nous semble devoir être traitée. L'interprétation chrétienne du marxisme, à laquelle se livre Polanyi, est une façon de comprendre la condition d'étrangeté qu'éprouve l'homme moderne face à lui-même ; cette interprétation permet aussi de voir dans le fascisme la négation même du socle judéo-chrétien qui fonde en Occident la communauté humaine authentique. En second lieu, nous aborderons la question du contenu et de la construction du socialisme. Si, pour Polanyi, le socialisme est la réponse chrétienne aux défis posés par l'âge industriel, en revanche, la démocratie n'est pas une simple "superstructure" du capitalisme : une ambiguïté de l'œuvre de Marx est alors soulignée. Le socialisme, selon Polanyi, est l'extension du constitutionnalisme à la sphère de l'économie. Aux mirages de l'économie de commandement, Polanyi, dès 1922, oppose déjà la nécessité éthique d'une économie décentralisée impliquant la responsabilité des producteurs-associés. D'ailleurs, la signification du socialisme semble liée à la façon politique de l'instituer. Polanyi est hostile à la doctrine selon laquelle la stricte préservation de l'intérêt économique d'une classe sociale est à même d'assurer sa sauvegarde à long terme, car la lutte de classes doit tenir compte d'enjeux sociaux globaux. D'une façon générale, contre toute forme de déterminisme, singulièrement celui de la IIième internationale, Polanyi oppose la valeur de ce qui est dû aux choix conscients et responsables. Enfin, nous présenterons les débats anthropologiques qui marquèrent la seconde grande période de l'itinéraire de Polanyi. Jusqu'en 1936, il est possible d'inclure Polanyi dans le courant austro-marxiste ; après 1950, Polanyi critique l'idéologie économique qui caractérise nombre d'aspects du travail des sciences sociales. Les figures du travail de Marx qui sont inspirées par l'économisme occidental sont dénoncées par Polanyi ; mais Polanyi lui-même et certains membres de son école distinguent bien Marx d'Engels. Il n'en reste pas moins que les investigations de Polanyi sont une façon de conserver certains acquis du travail de Marx tout en s'émancipant du cadre de la dialectique. Popper lui-même reconnaît une dette envers Polanyi : celui-ci lui aurait montré les vertus d'un "nominalisme méthodologique" pour les sciences sociales dans les années 20. C'est cette même attitude qui inspire le programme Columbia des années 50 et qui provoque le rejet par certains marxistes de la méthode dite "substantive". Mais, ce que rejette Polanyi, ce n'est pas l'intérêt de l'analyse marxiste pour le capitalisme de son époque, c'est plutôt l'extension aux sociétés non-modernes de concepts imprégnés par la modernité ; c'est enfin, le refus de toute "loi" de développement social. Par où Polanyi, sans être cette façon d'anti-Marx à l'usage de "radicaux" pour les temps post-modernes, se révèle aussi pertinent qu'actuel. First, this is the critique of capitalism and fascism as the always possible extension of it seems we have to be treated. The Christian interpretation of Marxism by Polanyi is a way of understanding the condition of strangeness experienced by modern man in front of himself; This interpretation also makes it possible to see in fascism the very negation of the Jewish-Christian base which founds the authentic human community in the West. Second, we will address the question of the content and construction of socialism. If, for Polanyi, socialism is the Christian response to the challenges posed by the industrial age, democracy, on the other hand, is not a simple "superstructure" of capitalism: an ambiguity of Marx's work is underlined. Socialism, according to Polanyi, is the extension of constitutionalism to the sphere of the economy. To the mirages of the economy of command, Polanyi, already in 1922, already opposes the ethical necessity of a decentralized economy involving the responsibility of the associate producers. Moreover, the meaning of socialism seems to be linked to the political way of instituting it. Polanyi is hostile to the doctrine that the strict preservation of the economic interest of a social class is capable of ensuring its long-term safeguard, since the class struggle must take account of global social issues. In a general way, against all forms of determinism, particularly that of the Second International, Polanyi opposes the value of what is due to conscious and responsible choices. Finally, we will present the anthropological debates that marked the second major period of Polanyi's itinerary. Until 1936, it was possible to include Polanyi in the Austro-Marxist current; After 1950, Polanyi criticized the economic ideology that characterizes many aspects of social science work. The figures of Marx's work which are inspired by Western economism are denounced by Polanyi; But Polanyi himself and some members of his school distinguished Marx from Engels. The fact remains that Polanyi's investigations are a way of preserving certain of the achievements of Marx's work, while emancipating himself from the framework of the dialectic. Popper himself acknowledged a debt owed to Polanyi, who would have shown him the virtues of a "methodological nominalism" for the social sciences in the 1920s. It was this attitude that inspired the Columbia program of the 1950s, Provokes the rejection by certain Marxists of the so-called "substantive" method. But what Polanyi rejects is not the interest of Marxist analysis for the capitalism of his time, but rather the extension to modern societies of concepts imbued with modernity; Finally, the refusal of any "law" of social development. By which Polanyi, without being this way of anti-Marx to the use of "radicals" for the post-modern times, is as relevant as it is actual. Working paper or preprint
Economics; Sociology
Keywords: MARX; Karl; 1818-1883; communism; communisme; fascism; fascisme; matérialisme historique; socialism; totalitarisme; vitalisme

Une révolution bureaucratique britannique ? - Gales, Patrick LE; Scott, Alan (Una revolución burocrática británica ? Autonomía sin control o « freer markets, more rules »., 2008)
This article originated with a puzzle : how best to account for changes in the behavior of groups, organizations and individuals in Great Britain ? A detailed analysts of what Weber and Polanyi identified as interdependencies between state and market, and of the state's role in creating the market, led to the decision to adapt the notion of bureaucratic revolution put forward by Weber. We argue that the British bureaucratic revolution is reflected in the fact that the state plays an essential role in social change by creating rules and institutions that lastingly orient actors' behavior. The examples of health and local authorities are then used to identify mechanisms that were influential throughout a ten-year period specifically the introduction of competition features (rewards and punishments) and of auditing and inspection. If our interpretation is accurate, the effects of this bureaucratic revolution may well come to be felt in contexts other than Great Britain. (English)
Sociology; Political Science
Keywords: 1997-2010; Great Britain - social conditions - 1945-; WEBER; Max; 1864-1920; bureaucratization; economic policy; social goals; socioeconomics

Economie et Rationalite: Apports et limites de l'approche polanyienne. (Economics and Rationality: Contributions and Limits of Polanyian Approach. With English summary.) - Postel, Nicola; Sobel, Richard (Cahiers d'Economie Politique, 2008)
Polanyi analyzes the historical deployment of a "formal" economic science starting from the triptych "market-rarety-instrumental rationality". It reveals this triptych, and the knowledge which is devoted to it, as being a part of a question broader than should analyze a "substantial" economic science being interested in the triptych "need-nature-institution". If we can and must follow Polanyi in his criticism of economism suited to the first triptytic, we have more reserve to accept his solution of substitution, an heterogeneous mixture of naturalism and institutionalism, of essentialism and historicism. The thesis defended in the article is that it is necessary to be more Polanyian that Polanyi himself, and to develop an economy of the practical reason, base of an economic science reintroduced inside social sciences.
Sociology; Economics
Keywords: criticism of economism; formal economy; general economics

Karl Polanyi, le marché et le socialisme - Skornicki (2008)
La société est-elle condamnée à subir les lois du marché ? La publication d'Essais inédits de l'économiste Karl Polanyi permet de redécouvrir le (...)
History; Sociology
Keywords: capitalisme; fascisme; marché; socialisme

Le problème du désencastrement, The Problem of Disembeddedness - Velly, Ronan Le (Revue du MAUSS, 2007)
Cet article revient sur la réception du travail de Karl Polanyi par plusieurs chercheurs importants de la nouvelle sociologie économique. Il montre que Polanyi a fait l’objet de deux types de critiques ayant en commun de contester la possibilité du désencastrement. Ces critiques sont discutables, et il est possible de donner une explication des malentendus liés à cette question en distinguant deux notions complémentaires d’encastrement, la première insistant sur les conditions sociales à partir desquelles les échanges marchands sont nécessairement construits et la seconde décrivant les degrés variables de différenciation des économies., EN: This paper discusses the reception of Karl Polanyi’s work by some leading scholars of the New Economic Sociology. It shows that Polanyi has received two different kinds of criticisms that, both of which, contest that there can be such thing as disembeddedness. These criticisms are not very justified and it is possible to give an explanation of this misunderstanding by distinguishing between two different and complementary notions of embeddedness, a first one that puts the stress on the social conditions upon which economic transactions are necessary carried out and a second one that describes how much economies are differentiated.
Sociology
Keywords: critique; disembeddedness

Une fondation Polanyi : un projet toujours actuel, A Polanyi Foundation : Still Up To Date - Caillé, Alain (Revue du MAUSS, 2007)
La pensée de Polanyi peut être vue comme une sorte de lieu géométrique entre des courants de pensée de gauche très divers, de la gauche de gauche au centre gauche. Cet article montre comment, entre 1995 et 1999, le nom de Polanyi a en effet servi de point de ralliement à des dizaines d’intellectuels (sociologues, économistes, philosophes...) connus en France et en Europe, ce qui n’a pas été sans impact politique. Une perspective toujours d’actualité ?, Polanyi’s throught can be seen as some sort of smallest denominator common to diverse spheres of the Left ranging from ultra to central Left. The article shows how between 1995 and 1999 Polany’s name has permitted to gather dozens of well-known intellectuals (sociologists, economists, philosophers) in France and in Europe and how this gathering has had some political impact. A still urgent perspective ?
Sociology
Keywords: plural economy; radical social democracy; social-démocratie radicale; économie plurielle

Actualité de Karl Polanyi, The Actuality of Karl Polanyi - Caillé, Alain; Laville, Jean-Louis (Revue du MAUSS, 2007)
Que peut-on retenir de l’œuvre de K. Polanyi en comparaison, notamment, de celles de Marx ou de Weber ? Cet article fait le point à la fois sur les contributions historiques et anthropologiques de Polanyi à l’histoire du marché et sur son aspiration à un socialisme associationniste, et il conclut que, audelà des nécessaires rectifications et actualisations, K. Polanyi reste la source d’inspiration principale pour un socialisme radical à visage humaniste., What must be kept of K. Polanyi’s legacy as compared, especially, to those of Marx or Weber ? This article provides an evaluation both of the anthropological and historical contributions of Polanyi to the history of market(s) and of the present meaning of his advocacy of an associationist socialism. It concludes that, once the necessary corrections and rectifications are made, Polany remains our main resource to think a radical and democratic socialism with a humanist face.
Sociology
Keywords: capitalism; capitalisme; democracy; démocratie; marché; markets; socialisme associationniste; solidarity economy; économie solidaire

Mort et résurrection du capitalisme libéral, Death and Resurrection of Liberal Capitalism - Laval, Christian (Revue du MAUSS, 2007)
Pour comprendre La Grande Transformation de Karl Polanyi, il faut la replacer dans le contexte des années 1930 et 1940, époque de contestation générale du vieux libéralisme « manchestérien ». L’article compare les positions de quatre auteurs contemporains : Karl Polanyi, Joseph Schumpeter, Friedrich von Hayek et Walter Eucken. Cette comparaison montre d’abord que Polanyi n’était pas le seul à constater la fin du cycle libéral du capitalisme. Elle montre ensuite que la question portait aussi sur le type d’intervention de l’État. La nouveauté introduite par le néolibéralisme réside dans le fait que le marché n’est pas une nature, mais un ordre politiquement construit., ENG: To have an accurate reading of Karl Polanyi’s The Great Transformation, the reader should put his work back in its context of the 1930’s and 1940’s, in a time of widespread criticism of the old « manchesterian » liberalism. The text draws a parallel between the points of view of four contemporary writers : Karl Polanyi, Joseph Schumpeter, Friedrich Von Hayek et Walter Eucken. First and foremost, it shows that Polanyi was not the only writer to note the end of the liberal cycle of capitalism. Then, it emphasizes the fact that the debate was focused on the type of state intervention. The originality brought about by neoliberalism lies in the conception of market, which is no more considered as natural but as a political construction.
Sociology
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; SCHUMPETER; Joseph Alois; 1883-1950; liberal capitalism; neoliberalism

Karl Polanyi, une biographie intellectuelle - Maucourant, Jérôme (Revue du MAUSS, 2007)
I will endeavor here to retrace the major stages of life and career of Karl Polanyi and the genesis of his main ideas in the first part of the TWENTIETH century marked both by the occurrence of major disasters and the Effacement of the first market society that had taken shape in the nineteenth century.
Sociology; Political Science
Keywords: biography; capitalisme; démocratie; marché; socialisme

Le marché, une institution entre économie et histoire - Maucourant, Jérôme (Cahiers lillois d'économie et de sociologie, 2007)
"L'hypothèse de l'article est la suivante : il n'est pas possible de parler rigoureusement d'un concept de « marché » en science économique, car ce concept est en réalité une notion floue, au mieux ambivalente. En revanche, le recours à d'autres sciences sociales, comme l'histoire et la sociologie, peuvent aider à la construction d'un concept de marché. Ainsi, le travail de Karl Polanyi et les travaux d'historiens contemporains, notamment ceux d'Alain Guéry, semblent utiles pour mieux distinguer le marché propre à la « société de marché » au sens de Polanyi des marchés caractéristiques des économies archaïques ou d'Ancien régime. L'histoire des idées et la réhabilitation du travail de Montchrestien, contre le jugement hâtif de Schumpeter, est mobilisée pour illustrer l'hypothèse de l'article. Il est enfin suggéré que ni l'approche en terme d'équilibre général, ni les travaux d'Israël Kirzner n'ont eu de valeur heuristique en ce qui concerne la présente problématique." ENG translation: "The topic of the paper consists in arguing that it is not yet possible to have a rigourous concept of « market », as so far as economics is concerned. Nor equilibrilim theory nor kirznerian approach have a real interest for the precise task of conceptualising market as such. At best, « market » is a undetermined notion or, in some case, has even a double meaning (market place and selfregulating market). Nevertheless, thanks to other social science, i.e. history and sociology, il is possible to elaborate a concept of market. Works of Karl Polanyi, but also more recent contributions of a historian of french Ancien Régime economy, Alain Guéry, are usefull from this point of view. Then, a clear distinction seems to be done between market of modern « market society ». The paper insists also in giving ti the Montchrestien Traicté de l'Œconomie politique a importance denied by Schumpeter. "
Economics; Sociology
Keywords: economic theory; markets

Karl Polanyi et le processus institué de démocratisation politique, Karl Polanyi and the Instituted Process of Political Democratization - Mendell, Marguerite (Revue du MAUSS, 2007)
Cet article porte sur le « processus économique institué » de Karl Polanyi. Il s’appuie sur certains de ses écrits moins connus, qui précèdent et suivent la publication en anglais de la Grande Transformation, dans lesquels Polanyi insistait en particulier sur la capacité des individus et des collectivités à agir sur leur propre destinée. Ces écrits nous aident à conceptualiser les processus de transformation institutionnelle qui caractérisent la société contemporaine. Cet article s’intéresse à l’impact de la société dite civile sur l’innovation en matière de politiques ou d’institutions, sur les préconditions qui institutionnalisent, pour ainsi dire, ces pratiques – qui se transmettent ensuite horizontalement aux sous-systèmes institutionnels et verticalement aux institutions macro ou gouvernantes. ENG: This article bears on Polanyi’s « instituted economic process » and uses a range of not very well known articles published before and after The Great Transformation where Polanyi insisted on the capacity of individuals and communities to shape their own destiny. Here we are particularly interested in the impact of civil society on political innovation which percolates both along horizontal or vertical lines.
Economics; Sociology
Keywords: instituted economic process

Karl Polanyi, Viviana Zelizer et la relation marchés-société - Steiner, Philippe (Revue du MAUSS, 2007)
After a brief study on the place given to Polanyi’s thought in contemporary economic sociology, the paper examines Zelizer’s works on money and her opposition to Polanyi’s thesis on embeddedness, grounded on the symetry between markets and social life.
Sociology
Keywords: ZELIZER; Viviana; embeddedness

Karl Polanyi et les monnaies modernes : un réexamen - Blanc, Jérôme (Contributions à une sociologie des conduites économiques, 2006)
Karl Polanyi a établi une célèbre distinction entre "all purpose money", caractéristiques des sociétés modernes, et "special purpose money", caractéristiques des sociétés anciennes. C'est la conception polanyienne des monnaies modernes qui est critiquée dans ce texte : non seulement elle conduit à considérer que les sociétés modernes ne connaissent pas de "special purpose money", mais en plus elle ne permet pas de renouveler la conception courante de la monnaie (sous-entendu moderne) qui en fait un moyen de paiement universel. ENG translation: Karl Polanyi has established a famous distinction between "all purpose money" characteristic of modern societies, and "special purpose money", characteristic of ancient societies. It is the Polish conception of modern currencies that is criticized in this text: not only does it lead to the view that modern societies do not know a "special purpose money", but also does not allow to renew the current conception of Currency (modern underlining) which makes it a universal means of payment.
Sociology
Keywords: Monnaie moderne. Pratiques monétaires. Polanyi. Monnaies parallèles. Fongibilité. Cloisonnements.; boundaries; fungibility; modern money; monetary uses; parallel currencies

L'ère de l'opulence selon Polanyi - Maucourant, Jérome; Vivel, Christel (Economies et sociétés, 2005)
L'article expose la problématique d'un texte peu connu de Polanyi datant de 1959. Prétextant un commentaire de L'ère de l'opulence de Galbraith, il soutient que le naturalisme de l'économie dominante nous interdit de comprendre la signification véritable de la rareté. Polanyi montre alors que les oppositions classiques entre liberté et égalité, économie et démocratie, peuvent être dépassées dans le cadre d'une société nouvelle abolissant la séparation institutionnelle de l'économique et du politique. Ces thèses de Polanyi sont imprégnées d'un aristotélisme tenant compte des déchirures sociales que furent le machinisme et les fascismes. KM: One aims at presenting a unknown Polanyi's text. Starting with a comment of the Affluent Society from Galbraith, we explain that the mainstream economics'naturalism prevents us from understanding the actual significance of scarcity. Polanyi shows that the classical oppositions between liberty and equality, economy and democracy can be overcame in the frame of a brand new society in which the institutional line between economics and politics should be abolished. This is sustained by an aristotelism that takes into account the social breaks produced by machinism and fascisms.
Economics; Sociology
Keywords: opulence; rareté

Proximité spatiale et relations science - industrie : savoirs tacites ou encastrement (Polanyi ou Polanyi) ?, Spatial proximity and relations between academic research and firms : tacit knowledge or embeddedness (Polanyi or Polanyi) ? - Grossetti, Michel; Bès, Marie-Pierre (Revue d’Économie Régionale & Urbaine, 2002)
RésuméLes notions d’encastrement et de savoirs tacites sont souvent utilisées dans des théories expliquant les effets de proximité spatiale dans les relations entre la recherche académique et les entreprises. Même si elles ont des origines proches (ne serait-ce que parce qu’elles ont été formulées à l’origine par deux frères, Karl et Michael POLANYI), elles ont des implications très différentes en ce qui concerne l’interprétation des effets de proximité. Dans un cas (l’encastrement), on peut généraliser l’explication aux effets de proximité dans les relations entre organisations alors que dans l’autre cas (savoirs tacites), l’explication se restreint aux échanges en matière de connaissance. L’analyse d’un corpus de cas de collaboration entre les laboratoires du CNRS et les entreprises plaide en faveur de la thèse de l’encastrement., ENG: The notions of embeddedness and tacit knowledge are often used in the theories explaining spatial proximity effects in the relations between academic research and firms. Even if the two notions have a close origin (they have been defined by two brothers, Karl and Michael POLANYI), they imply different views on spatial proximity effects. In one case (embeddedness), it is possible to generalize the explanation of spatial proximity effects to all kinds of relations between organizations. In the other case (tacit knowledge), only knowledge spillovers can be explained. The analysis of a set of cooperations between firms and french academic laboratories suggests that embeddedness thesis is better.Classification JEL : O18.
Sociology
Keywords: POLANYI; Michael; 1891-1976; embeddedness; encastrement; proximité; savoirs tacites; science-industrie; tacit knowledge

Le travail, la servitude et la vie. Avant Marx et Polanyi, Eugène - Vatin, François (Revue du MAUSS, 2001)
Sociology
Keywords: France; MARX; Karl; 1818-1883; history; labour

Pourquoi relire Karl Polanyi au XXIe siècle ? - Morvan-Roux, Solène; Servet, Jean-Michel; Tiran, André (L'Économie politique, 2022)
Karl Polanyi (1886-1964) est surtout connu pour son livre The Great Transformation, et en particulier pour une idée contenue dans celui-ci : la distinction entre une « économie intégrée dans les relations sociales » et « des relations sociales intégrées dans le système économique ». Selon cet auteur, les activités économiques et techniques n’étaient d’abord qu’une des nombreuses excroissances des activités humaines. L’économie archaïque a donc été au service des besoins humains. Mais, au fil du temps, influencés par la science économique dominante, les décideurs politiques ont acquis la conviction que les marchés se régulaient d’eux-mêmes pour autant que les lois et les règlements ne les en empêchent. Peu à peu, à mesure que la pensée fondée sur le libre marché s’étendait à l’ensemble de la société tout comme le règne de la machine, les humains et la nature ont été considérés comme des marchandises appelées « travail » pour ceux-ci et « terre » ou « ressources naturelles » pour celle-là. L’« économie de marché » avait transformé la société humaine en une « société de marché ». La finance et la monnaie ont joué un rôle généralement sous-estimé dans cette transformation ; un rôle que Karl Polanyi a particulièrement mis en avant et qui résonne quasi quotidiennement avec notre actualité.
Sociology; Political Science
Keywords: Great Transformation; The (Book); interdisciplinary research; market society

Penser les bouleversements du monde à partir de Karl Polanyi - Postel, Nicolas (Revue Française de Socio-Économie, 2022)
Sociology